Pengaruh Kemajuan Teknologi dan Edukasi Pasar Modal Syariah terhadap Minat Masyarakat Berinvestasi di Pasar Modal Syariah - Alfian Ade Putrawan; Maslichah Maslichah; Afifudin Afifudin (El-Aswaq, 2022)
The purpose of this study is to determine the effect of technological advances and Islamic capital marketeducation on public interest in investing in the Islamic capital market. The method used is a correlationalquantitative method with several stages of research which include distributing questionnaires, collecting data,and analyzing data. The questionnaire was tested using validity test, reality test, normality test,multicollinearity test, heteroscedasticity test, multiple linear regression analysis, F test, determination test (R2),and t test. The results of this study indicate that the variable of technological progress has a positive andsignificant effect on public interest in investing in the Islamic capital market. The Islamic capital marketeducation variable has a positive and significant effect on public interest in investing in the Islamic capitalmarket.